Financial Reporting Quality and Investment Efficiency of Private Firms in Emerging Markets - Chen, Feng; Hope, Ole-Kristian; Li, Qingyuan; Wang, Xin (The Accounting Review, 2011)
ABSTRACT Prior research shows that financial reporting quality (FRQ) is positively related to investment efficiency for large U.S. publicly traded companies. We examine the role of FRQ in private firms from emerging markets, a setting in which extant research suggests that FRQ would be less conducive to the mitigation of investment inefficiencies. Earlier studies show that private firms have lower FRQ, presumably because of lower market demand for public information. Prior research also shows that FRQ is lower in countries with low investor protection, bank-oriented financial systems, and stronger conformity between tax and financial reporting rules. Using firm-level data from the World Bank, our empirical evidence suggests that FRQ positively affects investment efficiency. We further find that the relation between FRQ and investment efficiency is increasing in bank financing and decreasing in incentives to minimize earnings for tax purposes. Such a connection between tax-minimization incentives and the informational role of earnings has often been asserted in the literature. We provide explicit evidence in this regard.